A systems‐based approach to the environmental risk assessment of multiple stressors in honey bees. (20th May 2021) - ,; More, Simon; Bampidis, Vasileios; Benford, Diane; Bragard, Claude; Halldorsson, Thorhallur; Hernández‐Jerez, Antonio; Bennekou, Susanne Hougaard; Koutsoumanis, Kostas; Machera, Kyriaki; Naegeli, Hanspeter; Nielsen, Søren Saxmose; et al.
Abstract: The European Parliament requested EFSA to develop a holistic risk assessment of multiple stressors in honey bees. To this end, a systems‐based approach that is composed of two core components: a monitoring system and a modelling system are put forward with honey bees taken as a showcase. Key developments in the current scientific opinion (including systematic data collection from sentinel beehives and an agent‐based simulation) have the potential to substantially contribute to future development of environmental risk assessments of multiple stressors at larger spatial and temporal scales. For the monitoring, sentinel hives would be placed across representative climatic zones and landscapes in the EU and connected to a platform for data storage and analysis. Data on bee health status, chemical residues and the immediate or broader landscape around the hives would be collected in a harmonised and standardised manner, and would be used to inform stakeholders, and the modelling system, ApisRAM, which simulates as accurately as possible a honey bee colony. ApisRAM would be calibrated and continuously updated with incoming monitoring data and emerging scientific knowledge from research. It will be a supportive tool for beekeeping, farming, research, risk assessment and risk management, and it will benefit the wider society. A societal outlook on the proposed approach is included and this was conducted with targeted social science research with 64 beekeepers from eight EU Member States and with members of the EU Bee Partnership. Gaps and opportunities are identified to further implement the approach. Conclusions and recommendations are made on a way forward, both for the application of the approach and its use in a broader context. Abstract : This publication is linked to the following EFSA Supporting Publications articles: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2021.EN-6608/full